2015
DOI: 10.1002/polb.23941
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanics of physically transient electronics: A step toward controlled transiency

Abstract: Transient electronics is a class of electronic devices designed to maintain stable operation for a desired and preset amount of time; and, undergo fast and complete degradation and deconstruction once transiency is triggered. Controlled and programmed transiency in solvent‐triggered devices is strongly dependent on chemical and physical interactions between the solvent and the device, as well as those within the device itself, among its constituent components. Mechanics of transiency of prototypical transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Mechanical properties of swelling PVA membranes were measured for up to 80 s of exposure to water, at 10 s intervals (Figure b). The swelling rate appeared to be slow for the first 40 s of exposure to water, which is in agreement with our previously reported analysis of mechanics of PVA swelling and degradation . Local rearrangement of molecules occurs during the first stage of swelling; thus, change in volume is minimal.…”
Section: Resultssupporting
confidence: 91%
“…Mechanical properties of swelling PVA membranes were measured for up to 80 s of exposure to water, at 10 s intervals (Figure b). The swelling rate appeared to be slow for the first 40 s of exposure to water, which is in agreement with our previously reported analysis of mechanics of PVA swelling and degradation . Local rearrangement of molecules occurs during the first stage of swelling; thus, change in volume is minimal.…”
Section: Resultssupporting
confidence: 91%
“…Lithium‐ion battery technology is a well‐established, mature, and commercialized technology; here, we are integrating a variation of this technology with our new approach toward transient electronics, which is ultimately based on a hybrid approach of physical redispersion of insoluble materials, and chemical dissolution of soluble ones. In our previous studies, we have reported electrical and mechanical properties of such hybrid systems. The transient primary Li‐ion batteries we report here incorporate this technology and are consist of electrodes comprise of active materials similar to those in conventional Li‐ion batteries while swelling force of the substrate/casing materials is utilized to introduce transiency through fragmentation and redispersion of the active materials.…”
Section: Introductionmentioning
confidence: 99%
“…As the solvent molecules penetrate through the substrate, swelling force is generated and increased to a point large enough to physically break the active materials layer [Fig. (e)] . Swelling of PVA and the associated force which breaks the active materials into pieces are essential to the transiency of the electrode; an identical sample of active materials (same area density) on polyvinyl acetate substrate (does not swell but dissolve in water) only curled and did not break or exhibit transiency (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While the PEO substrate is water-soluble, printed PEDOT:PSS electrodes are not. We demonstrated in previous studies that insoluble active electrodes might undergo disintegration by swelling-induced stress of the substrate [10,[55][56][57][58]. Here, the transiency of the all-organic electrodes in water was studied and is presented in Figure 4a.…”
Section: Transiencymentioning
confidence: 84%